IMPLEMENTASI TERAPI DZIKIR SEBAGAI INTERVENSI PSIKOTERAPI ISLAM DALAM MENGATASI GANGGUAN KECEMASAN UMUM - Syah, Ahmad Maujuhan (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
New students need to adjust to a completely unfamiliar new environment. They will experience significant environmental differences, such as Islamic boarding school regulations, intensive study activities, and more intensive study of yellow books. This new environment can trigger general anxiety, often referred to as Generalized Anxiety Disorder (GAD). This study aims to examine how to use structured dhikr. The method used is qualitative phenomenology. The results showed that new students, after practicing the structured dhikr method, experienced reduced anxiety and felt calmer in their worship. Dhikr helps fill this void by providing a sense of divine purpose. In this study, new students who previously felt confused and highly anxious began to feel closer to God after practicing dhikr regularly, which helped them rediscover the meaning of life.